Using National Incident-Based Reporting System Data for Strategic Crime Analysis - Faggiani, Donald (Journal of quantitative criminology, 1999)
The utility of the National Incident-Based Reporting System (NIBRS) forstrategic crime analysis has yet to be explored. The NIBRS represents anadvancement over existing reporting systems and possesses considerableutility to frontline law enforcement with respect to strategic crimeanalysis. This paper discusses the utility of the NIBRS for identifyinglocal and regional trends in narcotics related offenses. As an example, weselected four localities from the 1997 Virginia NIBRS data to examine trendsin the sale/distribution and possession of narcotics. Our analysis showsthat the NIBRS provides significantly more incident-related detail than hasheretofore been available for strategic crime analysis at the regional orstate level. Moreover, the NIBRS provides neighboring communities theopportunity to compare information on emerging crime patterns and criminalenterprises which extend beyond local boundaries. Finally, enhancing localreporting compliance by highlighting the strategic utility of the data tolocal law enforcement will ultimately ensure the quality of the data set,which can then be employed by larger entities as well as criminal justiceresearchers for policy development and planning.